The Application of Qawāʿid al-Ḥisān fī Tafsīr al-Qur’ān in the Verses of Islamic Family Law and Its Relation to Legislative Regulations in Indonesia - Romadhan, Muhammad Muhib Rofiqo Qaula; Khosim, Ali; Muhammad Zainal Arifin; Mohammad Athoillah (JIA (Jurnal Ilmu Agama), 2026)
This study aims to analyze the application of Principle Twenty-One (The Qur’an in its guidance corresponds to time and circumstances in its rulings that are based on custom and tradition), Principle Eighteen (Releasing and restricting guidance and misguidance), and Principle Twenty-Six (Qur’anic verses that contain limitations (qayd/exceptions/qualifications) cannot have their legal rulings applied unless those conditions or limitations are fulfilled, except in certain verses that are indeed exempted by other evidence) from the work Qawāʿid al-Ḥisān fī Tafsīr al-Qur’ān in the verses of Islamic family law. The discussion focuses on their relevance to Indonesian positive law. Using a qualitative-normative method with comparative analysis between classical fiqh and national regulations, this study shows that several family law verses, such as QS. al-Baqarah [2]: 229 and 231, contain a muthlaq–muqayyad structure that opens space for legal change in accordance with developments in time, place, and social conditions. Principle Twenty-One affirms that Qur’anic guidance in social matters refers back to ‘urf, so that the practices of khulu’, ṭalāq, and the prohibition of ḍirār undergo significant adjustment in the present time. Principle Eighteen indicates that verses which appear absolute are often explained by other verses through the mention of legal causes related to human behavior. Principle Twenty-Six affirms that a legal ruling does not apply without the fulfillment of its binding element, except where there is evidence that exempts it. In the Indonesian context, this dynamic is reflected in the transformation of the concept of khulu’ into a divorce lawsuit, the regulation of ṭalāq through court registration, and the criminalization of psychological violence and family neglect as stipulated in the UUPKDRT. This study concludes that the application of these three principles of interpretation affirms the flexibility of Islamic family law and its compatibility with national legal reform.